Preoperative Oral Health Screening Prior to Cardiovascular Intervention: A Case Report - Dwiyanti, Stephani; Benyamin, Benyamin; Zita, Maria; Ole, Maria RM; Wiranatha, Jennifer (Journal of Medicine and Health, 2024)
Valvular heart disease causes impaired function and decreases the quality of life. This condition could be managed surgically, but preoperative oral health screening is needed to eliminate oral infection. This paper aims to review common clinical findings in oral examination procedures, give an overview of the relationship between oral health and cardiovascular disease, and differentiate between pathological and typical findings in the oral cavity. A 34-year-old woman with valvular heart disease was referred for oral health evaluation and treatment before elective heart valve surgery. She was routinely medicated with Warfarin. She needed extraction of a fractured tooth, restoration of carious teeth, and scaling. Less urgent findings such as abfractions, gingival recession, malposed, and missing teeth could be treated after heart surgery. It was suggested that she not stop Warfarin and take Amoxicillin before dental procedures. In conclusion, general practitioners (GPs) play a significant role in the early detection of commonly found dental problems, especially in patients with cardiovascular disease who are about to undergo surgical intervention. GPs should be able to perform basic oral examinations, provide basic oral health education, know when to use antibiotic prophylaxis or discontinue anticoagulants wisely, and make timely referrals for patients requiring further dental management.